Internet Freedom Software and Illicit Activity Supporting Human Rights Without Enabling Criminals - Romanosky, Sasha (RAND Corporation, 2015)
This report examines the portfolio of tools funded by the State Department's Bureau of Democracy, Human Rights, and Labor that help support Internet freedom and assesses the impact of these tools in promoting U.S. interests (such as freedom of expression, freedom of the press, and the free flow of information) without enabling criminal activity.